EXPERT: transfer learning-enabled context-aware microbial community classification. Issue 6 (17th September 2022) - Chong, Hui; Zha, Yuguo; Yu, Qingyang; Cheng, Mingyue; Xiong, Guangzhou; Wang, Nan; Huang, Xinhe; Huang, Shijuan; Sun, Chuqing; Wu, Sicheng; Chen, Wei-Hua; Coelho, Luis Pedro; et al.
Abstract: Microbial community classification enables identification of putative type and source of the microbial community, thus facilitating a better understanding of how the taxonomic and functional structure were developed and maintained. However, previous classification models required a trade-off between speed and accuracy, and faced difficulties to be customized for a variety of contexts, especially less studied contexts. Here, we introduced EXPERT based on transfer learning that enabled the classification model to be adaptable in multiple contexts, with both high efficiency and accuracy. More importantly, we demonstrated that transfer learning can facilitate microbial community classification in diverse contexts, such as classification of microbial communities for multiple diseases with limited number of samples, as well as prediction of the changes in gut microbiome across successive stages of colorectal cancer. Broadly, EXPERT enables accurate and context-aware customized microbial community classification, and potentiates novel microbial knowledge discovery.